Obstetric Medicine: the protocol for a prospective three-dimensional cohort study to assess maternity care for women with pre-existing conditions (ForMaT) - Jost, Elena; Kosian, Philipp; Greiner, Gregory Gordon; Icks, Andrea; Schmitz, Marie-Therese; Schmid, Matthias; Merz, Waltraut M. (Frontiers in Medicine, 2024)
Background Pregnancies in women with pre-existing medical conditions are on the rise. These pregnancies are characterized by an increased rate of maternal and perinatal complications, which can result in higher health care expenditures and altered pregnancy experiences. The purpose of this study is to integrally analyze maternity care for women with pre-existing conditions in the framework of a risk-adapted, interdisciplinary care by recording three substantial parts of maternity care: (1) maternal and perinatal outcome; (2) hospital costs and reimbursements covering the period from preconception counseling or initial antenatal visit to discharge after birth; and (3) women’s experience of reproductive choice and becoming a mother in the presence of a pre-existing condition. Methods In this observational, prospective, longitudinal, and monocentric cohort study, we aim to include a total of 1,500 women over a recruitment period of 15 months. Women registering for care at the Department of Obstetrics and Prenatal Medicine, University Hospital Bonn, Germany, are allocated to three groups based on their health and risk status: women with pre-existing conditions, as well as healthy women with obstetric risk factor and healthy women with a low-risk pregnancy. Participants are observed from time of initial consultation until discharge after birth. Analysis focuses on (1) maternal and perinatal outcome, especially rate of severe maternal and neonatal morbidity; (2) costs and reimbursements; and (3) surveys to capture of women’s experience and health-related quality of life during the time of reproductive choice, pregnancy, and childbirth in the presence of pre-existing medical conditions. Discussion With its complex three-dimensional design, the ForMaT-Trial is aiming to provide a comprehensive analysis of pregnancy and childbirth in women with pre-existing conditions. The results may serve as a basis for counseling and care of these women. By analyzing costs of specialized care, data for discussing reimbursement are generated. Lastly, our results may increase awareness for the perception of reproductive choice, pregnancy and motherhood in this continuously rising population. Clinical trial registration: German Clinical Trials Register, DRKS00030061, October 28, 2022.